From 466 to 90 - Regulation or Education? Policy Options for a Single-use Plastic Bag Consumption Reduction in the Slovak Republic - KARELOVÁ, Klaudia (Journal of Environmental Management and Tourism; Vol 8 No 5 (2017): JEMT Volume VIII Issue 5(21) Fall 2017, 2018)
The world has noticed strong evidence on rising plastic bag consumption, as well as its harmful impacts to the environment, wildlife and human health. In terms of the European Union, new Directive was introduce to combat extremely high consumption of single-use plastic bags in member countries. In regard of the Slovak legislation, the National Council is currently approving new proposal banning free distribution of plastic bags which is probable to come into force in 2019. The paper offers analysis of two scenarios for introducing a new charging mechanism to reduce single-use plastic bag consumption in the Slovak Republic. The author emphasizes the Scenario 1 where all retailers are included in the mechanism, as it provides society with higher benefits than the Scenario 2 where large retailers are exempt from imposing a charge on plastic bag sale. All in all, the policy option of imposing a levy on single-use plastic bag consumption in Slovakia will meet EU targets and will be in compliance with the Directive 2015/720.